Assessment of nutrient and heavy metal concentrations in sediments and macrophytes of the Oroma wetland, Nigeria - Ogugbue-Jason, Victoria Tovo; Ifeanyichukwu Clinton, Ezekwe (Macedonian Journal of Ecology and Environment, 2020)
This study assessed the nutrient and heavy metal concentrations in sediments and macrophytes of the Oroma wetland, University of Port Harcourt, Nigeria. A map representation of the wetland was assigned North-South (N-S) grid lines and six numbers were randomly selected to represent the six sampling points – SS1, SS2, SS3, SS4, SS5 and SS6. Sediment and three macrophytes (Alchornea cordifolia, Sacciolepis africana, and Harungana madagascariensis) that were present in each grid were collected and analyzed. Results showed that the wetland sediment was polluted with cadmium (4.80-54.10 mg/kg) and lead (98.60-175.30 mg/kg) whereas, only the sediment obtained from SS1 was polluted with nickel (75.9 mg/kg). In the sediment, cadmium posed a very high ecological risk; lead posed a considerable ecological risk whereas, the other heavy metals analyzed in this study posed low ecological risks. SS5 and SS6 had very high ecological risks whereas, the other sampling sites had moderate ecological risks. Cadmium, cobalt, copper, iron, zinc and arsenic were in same cluster in sediment based on cluster analysis while, chromium and nickel were assigned a separate cluster. The macrophytes collected from each site bioaccumulated the heavy metals from the sediment albeit at varying levels. Major sources of the nutrient and heavy metal burden in Oroma wetland were identified as runoffs and effluents from the adjoining University, residential areas, farmlands, car wash centers, generator houses, slaughter houses, metal dump sites, automobile maintenance shops, and vehicle exhaust. This study has highlighted the pollution status of the Oroma wetland sediment, the heavy metal burden of its macrophytes and the ecological risks posed by these heavy metals which have serious public health and ecological consequences.